Efficient conversion of leather tanning waste to biodiesel using crab shell-based catalyst: WASTE-TO-ENERGY approach. (August 2021) - Yuliana, Maria; Santoso, Shella Permatasari; Soetaredjo, Felycia Edi; Ismadji, Suryadi; Ayucitra, Aning; Gunarto, Chintya; Angkawijaya, Artik Elisa; Ju, Yi-Hsu; Truong, Chi-Thanh
Abstract: To promote the use of waste-originated resources in biodiesel production, this study proposes the utilization of leather tanning waste (LTW) and crab-shell (CS) waste as the respective lipid source and catalyst material. The obtained CS-based calcium oxide (CaO) has comparable textural properties with those of existing waste-based catalysts and shows high catalytic activity for the conversion of LTW to biodiesel. The optimum yield of fatty acid ethyl esters (FAEE) is predicted at 97.9 wt%, while it is experimentally observed at 98.7 ± 0.4 wt% (purity of 98.6 ± 0.4 wt%) using the following operating condition: reaction time t = 3.58 h, catalyst amount m c = 3.87 wt%, and a molar ratio of ethanol to LTW m eo = 12:1. The CS-based CaO shows good reusability with FAEE yield staying above 90 wt% for four cycles. The fuel properties of LTW-based biodiesel meet ASTM D6751 and ASTM D975-08 standards, with the ethyl ester ranging from C14 to C20. Graphical abstract: Image 1 Highlights: The tannery and aquaculture wastes are successfully utilized to produce biodiesel. The highest biodiesel yield of 98.7 wt% is achieved from this waste-to-energy act. The optimum operating condition: t = 3.58 h, m c = 3.87 wt%, and m eo = 12:1. The crab shell-based CaO has good reusability up to the fourth run (yield > 90 wt%). The properties of the resulting biodiesel are following the standard of ASTM D6751 .